Harmony Harmony Amidst Disruption: Islamic Approaches to Managing Technological Influences in the Family - Hikmah, Nurul; Sa'diyah, Halimatus (Proceedings Conference Psychology and Flourishing Humanity, 2025)
In the modern era filled with rapid technological developments, families often face challenges in maintaining harmony amidst the increasingly dominating influence of technology. This article discusses the Islamic approach in managing the influence of technology in the family with the aim of maintaining household harmony. Through understanding Islamic values and the principles contained therein, this article explains how Muslim families can face technological disruption wisely. Education and awareness about the impact of technology, open communication between family members, implementing healthy boundaries in technology use, and using technology for beneficial purposes are some of the approaches described in this article. By implementing these approaches, it is hoped that families can maintain harmony and strengthen Islamic values in their daily lives.